Cholera prevention, control strategies, challenges and World Health Organization initiatives in the Eastern Mediterranean Region: A narrative review - Buliva, Evans; Elnossery, Sherein; Okwarah, Patrick (Elsevier, 2023)
The resurgence of cholera is presenting unusual challenges in the Eastern Mediterranean Region (EMR), where it is considered endemic in nine-member states. The risk of a cholera outbreak spreading to non-endemic countries remains high. We discuss the regional trends of cholera, regional burden, and challenges with a focus on World Health Organization (WHO) initiatives in the region that could be useful in preventing and controlling the disease in similar contexts. Despite significant progress in the control of cholera worldwide, the disease continues to be a major public health problem across the region, where it constitutes both an emerging and re emerging threat. Recurring cholera outbreaks are an indication of deprived water and sanita tion conditions as well as weak health systems, contributing to the transmission and spread of the cholera infection. We note that despite the challenges in eliminating cholera in the region, effective implementation of the proposed WHO EMR Strategic framework, among other measures, could sustain the region’s cholera prevention, preparedness, and response needs.
Available online 21 April 2023 2405-8440/© 2023 Published by Elsevier Ltd. This is an open access article under the CC BY-NC-ND IGO license (http://creativecommons.org/licenses/by-nc-nd/3.0/igo/).
Keywords: Cholera; WHO Eastern Mediterranean Region; Prevention and control WHO Strategic framework